2009
DOI: 10.1016/j.biortech.2009.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Removal of persistent organic pollutants from micro-polluted drinking water by triolein embedded absorbent

Abstract: a b s t r a c tA new biomimetic absorbent, cellulose acetate (CA) embedded with triolein (CA-triolein), was prepared and applied for the removal of persistent organic pollutants (POPs) from micro-polluted aqueous solution. The comparison of CA-triolein, CA and granular activated carbon (GAC) for dieldrin removal was investigated. Results showed that CA-triolein absorbent gave a lowest residual concentration after 24 h although GAC had high removal rate in the first 4 h adsorption. Then the removal efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 23 publications
0
18
0
2
Order By: Relevance
“…According to the principle of similarity and intermiscibility, triolein has a strong absorbability for trace level of hydrophobic organic pollutants. Previous studies Liu et al, 2009;Huo et al, 2005;Ru et al, 2007;Qu, 2008) showed the preparation of a biomimetic adsorbent by embedding triolein into cellulose acetate (CA) spheres. The section structure is shown in Fig.…”
Section: Preparation and Application Of Lipoid Adsorbentmentioning
confidence: 99%
“…According to the principle of similarity and intermiscibility, triolein has a strong absorbability for trace level of hydrophobic organic pollutants. Previous studies Liu et al, 2009;Huo et al, 2005;Ru et al, 2007;Qu, 2008) showed the preparation of a biomimetic adsorbent by embedding triolein into cellulose acetate (CA) spheres. The section structure is shown in Fig.…”
Section: Preparation and Application Of Lipoid Adsorbentmentioning
confidence: 99%
“…They are characterized by pronounced persistence against chemical/biological degradation, high environmental mobility, strong tendency for bioaccumulation in human and animal tissues, and significant impacts on human health and the environment, even at extremely low concentrations [1].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effects of these ubiquitous compounds are not only limited to human but are extended to environment (Anwar et al, 2011). Due to their chemical properties, they pose significant impact on human health and environment even at low concentrations (Liu et al, 2009). Pesticides when released into the environment have different environmental fate as they may fall into different environmental compartments such as in air, soil or water.…”
Section: Introductionmentioning
confidence: 99%